Tres notas sobre el lenguaje cinematográfico de Pasolini en el Decamerón - Santamaría Aceituno, Julio C. (Cuadernos de Filología Italiana, 2011)
In these brief notes there will be analyzed the own elements of the cinematographic language: editing, sound, narrative structure. Pasolini uses these element to achieve a popular vision of Boccaccio’s book.